2005
DOI: 10.1093/toxsci/kfi322
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Effects of Bisphenol A May Be Mediated by Somatostatin Subtype 3 Receptors in Some Regions of the Developing Rat Brain

Abstract: Considerable attention has been focused on environmental disruptors such as the xenoestrogen bisphenol A, which influences reproductive, developmental, and cognitive activities through its interaction with specific neuromediating systems in an estrogen-like fashion. In the present study, the effects of this xenoestrogen proved to be preferentially directed toward hypothalamic and extrahypothalamic somatostatin receptor subtype 3, which displayed a higher binding affinity of its specific nonpeptide agonist L-79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In the periventricular and ventromedial (VMN) nuclei, increased levels of somatostatin receptor 2 were found with BPA exposure at PND 10, and in the periventricular nucleus at PND 23 (Facciolo, Alo et al 2002). BPA-related Increases in the expression of somatostatin receptor 3 were also reported in the PND 7 VMN and ARC (Facciolo, Madeo et al 2005). Dioxin reportedly reduced GAD 67 expression in the preoptic area (POA) at PND 3, thereby reducing the naturally occurring sex difference in the rostral portion of the POA (Hays, Carpenter et al 2002).…”
Section: Resultsmentioning
confidence: 81%
“…In the periventricular and ventromedial (VMN) nuclei, increased levels of somatostatin receptor 2 were found with BPA exposure at PND 10, and in the periventricular nucleus at PND 23 (Facciolo, Alo et al 2002). BPA-related Increases in the expression of somatostatin receptor 3 were also reported in the PND 7 VMN and ARC (Facciolo, Madeo et al 2005). Dioxin reportedly reduced GAD 67 expression in the preoptic area (POA) at PND 3, thereby reducing the naturally occurring sex difference in the rostral portion of the POA (Hays, Carpenter et al 2002).…”
Section: Resultsmentioning
confidence: 81%
“…Several studies have described adverse effects of BPA exposure on the reproductive system [47,67,71], progression of physical puberty [29], adult behaviors [16,40], enhanced risks of obesity [45,64], type 2 diabetes mellitus [4], and tumor development [8]. In addition, adverse effects of pre-and perinatal BPA exposure on brain development [20,26,32,33,42,58,66] and neurobehavioral development [1,2,21,25,35,50,51,74] are of growing concern, among which the disturbance of monoaminergic system development [1,32,35,50] and the lack of brain and/or behavioral sexual dimorphism [21,33,42,58] should be particularly noted. However, some studies argued that there are minimal or no adverse effects of BPA [31,34,60], which leaves room for discussion regarding the risk of BPA exposure on human health and development.…”
Section: Introductionmentioning
confidence: 99%
“…The initial studies used a short‐term higher dose, as well as a long‐term lower dose of 40 µg/kg d. Some studies included a comparison estrogen (Della Seta et al, 2006). Two other papers were directed at the examination of estrogen‐related brain mechanisms (Facciolo et al, 2002, 2005).…”
Section: Developmental Toxicity Studies In Laboratory Rodentsmentioning
confidence: 99%
“…Somatostatin receptors colocalize on the cell membrane with the membrane estrogen receptor (GP 30), as well with a receptor for the inhibitory neurotransmitter GABA (GABAα receptor). Somatostatin receptor genes have an estrogen response element and BPA was shown to induce somatostatin receptor subtype 3 (sst3) expression in hypothalamic areas in a manner that interacted with the effect of specific GABA agonists (Facciolo et al, 2005). In other studies, BPA was found to bind to sst2 in limbic areas of the brain of PND 10 and PND 23 rats (Facciolo et al, 2002).…”
Section: Developmental Toxicity Studies In Laboratory Rodentsmentioning
confidence: 99%